Work Stress Among University Teachers : Gender and Position Differences - Slišković, Ana (Array, 2011)
The aim of this study was to investigate exposure to stress at work in university teachers and see if there were differences between men and women as well as between positions. The study was carried out online and included a representative sample of 1, 168 teachers employed at universities in Croatia. This included all teaching positions: assistants (50 %), assistant professors (18 %), associate professors (17 %), and full professors (15 %). Fifty-seven percent of the sample were women. The participants answered a questionnaire of our own design that measured six groups of stressors: workload, material and technical conditions at work, relationships with colleagues at work, work with students, work organisation, and social recognition and status. Women reported greater stress than men. Assistant professors, associate professors, and full professors reported greater stress related to material and technical conditions of work and work organisation than assistants, who, in turn, found relationships with colleagues a greater stressor. Full professors, reported lower exposure to stress at work than associate professors, assistant professors, and assistants.